An Introduction to the International Criminal Court (Third Edition) - Schabas, William A (Cambridge University Press, 2013)
The Rome Statute provides for the creation of an international criminal court with power to try and punish for the most serious violations of human rights in cases when national justice systems fail at the task. It constitutes a benchmark in the progressive development of international human rights, whose beginning dates back more than fifty years, to the adoption on 10 December 1948 of the Universal Declaration of Human Rights by the third session of the United Nations General Assembly.2 The previous day, on 9 December 1948, the Assembly had adopted a resolution mandating the International Law Commission to begin work on the draft statute of an international criminal court,3 in accordance with Article VI of the Genocide Convention.